Effects of Lidocaine Oropharyngeal Spray Applied Before Endotracheal Intubation on QT Dispersion in Patients Undergoing Coronary Artery Bypass Grafting: A Prospective Randomized Controlled Study - Bilgi,Murat (2020)
Abstract Objective: To investigate the effects of lidocaine oropharyngeal spray applied before endotracheal intubation on hemodynamic responses and electrocardiographic parameters in patients undergoing coronary artery bypass grafting. Methods: A total of 60 patients who underwent coronary artery bypass grafting surgery were included in this prospective randomized controlled study. Patients were randomly divided into two groups, the topical lidocaine group (administration of 10% lidocaine oropharyngeal spray, five minutes before laryngoscopy and endotracheal intubation) and the control group. Both groups were compared with each other in terms of main hemodynamic parameters including mean arterial pressure and heart rate, as well as P and QT wave dispersion durations, before and after endotracheal intubation. Results: The groups were similar in terms of age, gender, and other demographics and basic clinical characteristics. There was a statistically significant difference between the groups in terms of QT dispersion durations after laryngoscopy and endotracheal intubation. The increase in QT dispersion duration was not statistically significant in the topical lidocaine group, whereas the increase in QT dispersion duration was statistically significant in the control group. When the groups were compared in terms of P wave dispersion durations, there were significant decreases in both groups, but there was no significant difference between the groups. Conclusion: Our study revealed that the topical lidocaine administration before endotracheal intubation prevented increase of QT dispersion duration in patients undergoing coronary artery bypass grafting. Trial Registration: NCT03304431